Molecular characterization of NDM-1 producing Enterobacteriaceae isolates in Singapore hospitals - Teo, Jeanette (World Health Organization, 2012)
OBJECTIVE: In this study, we molecularly characterized 12 NDM-1 producing clinical Enterobacteriaceae (Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae) isolates that were part of a collection of non-carbapenem susceptible isolates obtained during a one-year period. These isolates were obtained from four local general hospitals in Singapore. METHODS: Polymerase chain reaction (PCR) assays and sequencing was used to determine the presence of β-lactamase encoding genes (bla) including bla(NDM-1) and plasmid-mediated quinolone and aminoglycoside resistance determinants. Conjugation experiments were performed to determine the transferability of bla(NDM-1). Isolate relatedness was determined by multilocus sequence typing (MLST). RESULTS: The isolates were completely resistant to the second- and third-generation cephalosporins tested as well as carbapenems. Susceptibility profiling of the isolates indicated that 100% retained susceptibility to tigecycline while 11/12 (91.7%) were susceptible to colistin. The bla(NDM-1) gene was encoded on plasmids that were easily transferable. None of the patients had a travel history to countries where NDM-1 has been reported. The isolates appear clonally unrelated with MLST, revealing a diversity of clonal types among the Klebsiella pneumoniae and Escherichia coli isolates. CONCLUSION: The ease of NDM-1 plasmid transmissibility may help their dissemination among the Enterobacteriaceae. Although it appears that the isolates are clonally unrelated, epidemiological links cannot be fully excluded without further research.